Tuberculosis non-communicable disease comorbidity and multimorbidity in public primary care patients in South Africa - Peltzer, Karl (African Journal of Primary Health Care and Family Medicine, 2018)
Background: Little is known about the prevalence of non-communicable disease (NCD) multimorbidity among tuberculosis (TB) patients in Africa. Aim and setting: The aim of this study was to assess the prevalence of NCD multimorbidity, its pattern and impact on adverse health outcomes among patients with TB in public primary care in three selected districts of South Africa. Methods: In a cross-sectional survey, new TB and TB retreatment patients were interviewed,and medical records assessed in consecutive sampling within 1 month of anti-TB treatment. The sample included 4207 (54.5% men and 45.5% women) TB patients from 42 primary care clinics in three districts. Multimorbidity was measured as the simultaneous presence of two or more of 10 chronic conditions, including myocardial infarction or angina pectoris, arthritis, asthma, chronic lung disease, diabetes mellitus, hypertension, dyslipidaemia, malignant neoplasms, tobacco and alcohol-use disorder. Results: The prevalence of comorbidity (with one NCD) was 26.9% and multimorbidity (with two or more NCDs) was 25.3%. We identified three patterns of multimorbidity: (1) cardiometabolic disorders; (2) respiratory disorders, arthritis and cancer; and (3) substance-use disorders. The likelihood of multimorbidity was higher in older age, among men, and was lower in those with higher education and socio-economic status. The prevalence of physical health decreased, and common mental disorders and post-traumatic stress disorder increased with an increase in the number of chronic conditions. Conclusion: High NCD comorbidity and multimorbidity were found among TB patients predicted by socio-economic disparity
African Journal of Primary Health Care & Family Medicine
Keywords: Tuberculosis non-communicable desease; Comorbity and multimorbity; Public primary care patients; South Africa; Tuberculosis